Why Indonesia Prefers A Mono-Religious Education Model? A Durkhemian Perspective - Mohamad Yusuf (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
This work aims to investigate the preference of the Indonesian for a specific type of religious education model, and to provide a theoretical understanding of this preference. In particular, this study aims to answer two research questions: How do Indonesian practice mono-religious education model? How should this practice be understood from Durkheim’s concept of mechanical solidarity? Three models of ethnographical study were conducted to answer the research questions: Analysing the state’s law on education, particularly with regard to religious education, in-depth interviews with school’ managers (Kepala Sekolah) and religious education teachers as well as the students. This study found that Indonesia prefers a mono-religious education model, as shown in the State's laws on education and the practice of religious education in schools. Unlike previous studies that mainly describe the practice of certain model of religious education, this study offers conceptual understanding of the practice of religious education by Durkheim's notions of mechanical solidarity. The mono-religious model is a social fact because it consists of the norms and values that are practised by and commonly found in all members of society. Comparative studies on the practice of religious education in Muslim countries might be needed as this mono-religious education model is a common practice by Muslim societies.